Implementasi Metode Kolaboratif Dalam Pembelajaran Pendidikan Agama Islam Untuk Meningkatkan Partisipasi Siswa - Amara, Ressa; Asy’Ari, Hasyim; Anwar, Muhammad Saidun (Jurnal Keislaman, 2025)
This study aims to analyse the implementation of collaborative methods in learning Islamic religious education to increase student participation. The research method used in this study is field qualitative method. Collaborative method is an approach that emphasises cooperation between individuals or groups to achieve a common goal. Collaborative method in learning Islamic Religious Education (PAI) refers to a learning approach that prioritises cooperation between students in groups to achieve common goals in learning. In this method, students are invited to discuss with each other, share knowledge, and work together in solving tasks or problems related to Islamic learning materials. A concrete example in the application of collaborative methods by doing practical tasks to students. Factors affecting success in the application of collaborative methods in Islamic learning depend heavily on student participation. And a conducive classroom atmosphere is a factor in the success of collaborative learning methods.